The Effect Of Vibration On User Comfort In Motor Vehicles - pratama, yuki alvandi; munif, moh. abdul; delpero, M arif; siallagan, rama roki; Hasibuan, Fardin (Universitas Riau Kepulauan, 2025)
Vibration is an unavoidable physical phenomenon in motor vehicle operation and is a dominant factor affecting user comfort. Excessive and prolonged exposure to vibration can trigger various negative responses in humans, ranging from fatigue and physiological discomfort to long-term health risks such as musculoskeletal and neurological disorders. This paper presents a comprehensive review of the effects of vibration on the comfort of motor vehicle users. The discussion includes the identification of vibration sources (internal and external), the mechanisms of vibration transmission through the vehicle structure, and the biomechanical response of the human body to whole-body vibration (WBV). In addition, this paper reviews vibration measurement and analysis methods based on international standards, analyzes the physiological and psychological impacts of vibration, and discusses vibration mitigation strategies applied in modern vehicle design, including passive, semi-active, and active suspension systems, as well as ergonomic seat design. Case studies of mitigation technology applications are also included to provide a practical overview. Finally, this paper identifies existing challenges and future research directions in an effort to improve vehicle user comfort and well-being.